Pengaruh Struktur Modal terhadap Harga Saham Dimoderasi Ukuran Perusahaan Perbankan BEI 2022-2024 - Luthfia Nur Hidayatul Husna; M. Mustaqim; Cynthia Eka Violita; Achmad Zaki (Pustaka Bangsa Indonesia, 2026)
This study aims to examine the effect of capital structure, measured by the Debt-to-Equity Ratio (DER) and Debt-to-Asset Ratio (DAR), on stock prices, as well as to investigate the moderating role of firm size in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The study employs a quantitative approach with a causal research design. The research population comprises all banking companies listed on the IDX, from which a sample of 19 firms was selected using purposive sampling, resulting in 57 firm-year observations over the three-year study period. The data were analyzed using panel data regression and Moderated Regression Analysis (MRA) with the assistance of EViews software. The findings indicate that the Debt-to-Equity Ratio (DER) has a significant negative effect on stock prices, whereas the Debt-to-Asset Ratio (DAR) exerts a significant positive effect on stock prices. Furthermore, firm size significantly moderates the relationship between DER and stock prices by attenuating its negative effect, while also moderating the relationship between DAR and stock prices by weakening its positive effect. Simultaneously, DER, DAR, firm size, and their interaction terms have a significant effect on stock prices, with an adjusted R² of 34.41%. These findings suggest that investors' valuation of banking stocks is influenced not only by firms' capital structure but also by firm size, which serves as an important contextual factor in assessing investment risk.